PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS (HOTS) BERBANTUAN WORDWALL PADA MATERI IPAS KELAS IV SD - Husniatun Na'miyah; Ika Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a Higher Order Thinking Skills (HOTS)-based assessment instrument using the Wordwall platform for fourth-grade elementary school science. The background of this study is based on the need for assessment innovation in the digital era because teachers still often use conventional instruments that only measure memory and comprehension abilities. The study uses a 4D development model that includes the stages of define, design, develop, and disseminate. Data collection techniques include interviews, observations, expert validation, and student test results. The validation results from material experts, evaluation experts, and language experts show that the instrument obtained an average feasibility of 93.13%, categorized as very feasible. Field trials on 15 students resulted in an average score of 75.53, indicating that the instrument is effective for measuring students' higher-order thinking skills. The Wordwall-based digital instrument is also considered capable of increasing student engagement through interactive and engaging displays. Thus, the developed HOTS-based assessment instrument is declared valid and effective for use in science learning. Further research is recommended to involve a larger sample, add a variety of question formats, and conduct empirical validity and reliability analyses to improve the quality of the instrument.